1979
DOI: 10.1097/00000658-197908000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Sex Hormone Binding Globulin as a Reliable Indicator of Hormone Dependence in Human Breast Cancer

Abstract: One hundred nine pre- and postmenopausal mammary carcinoma cases were studied to elucidate the role of sex hormone binding globulin (SHBG) in the hormone dependence of human breast cancer. Our findings indicate that there is a significant negative correlation between SHBG binding capacity and plasma testosterone concentration. All patients with high SHBG titers were found to be cytosol estrogen receptor (CER) positive and the plasma SHBG binding capacity of CER positive was significantly higher than that of CE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Murayama and co-workers (Murayama et al 1978) first observed a correlation between SHBG and estrogen receptor (ER) in postmenopausal breast cancer patients, but not in ER-positive premenopausal breast cancer patients. This finding was later confirmed by the same authors, who observed the simultaneous presence of high plasma SHBG concentrations and estrogen receptors in hormone-dependent breast cancer (Murayama et al 1979) and by Plymate and co-workers (Plymate et al 1984) who reported higher SHBG levels in ER-positive than in ERnegative breast-cancer patients.…”
Section: Shbg and Breast Cancer Riskmentioning
confidence: 56%
“…Murayama and co-workers (Murayama et al 1978) first observed a correlation between SHBG and estrogen receptor (ER) in postmenopausal breast cancer patients, but not in ER-positive premenopausal breast cancer patients. This finding was later confirmed by the same authors, who observed the simultaneous presence of high plasma SHBG concentrations and estrogen receptors in hormone-dependent breast cancer (Murayama et al 1979) and by Plymate and co-workers (Plymate et al 1984) who reported higher SHBG levels in ER-positive than in ERnegative breast-cancer patients.…”
Section: Shbg and Breast Cancer Riskmentioning
confidence: 56%
“…The KLK5 gene encodes a kallikrein serine protease, and its upregulation has been suggested to be an indicator of poor prognosis in breast and other cancers 44, 45. The SHBG gene codes for sex hormone binding globulin, and its upregulation is suggested to be a reliable indicator of hormone dependence in breast cancer 46, 47. The PPAPDC1A gene encodes an integral membrane phosphatic acid phosphatase and is upregulated widely in breast tumor tissues versus their adjacent nontumor tissues 48.…”
Section: Discussionmentioning
confidence: 99%
“…Further, high SHBG levels correlate with estrogen receptor positivity in hormone-dependent BRCA [81]. On a molecular level, connections between BRCA, SHBG and estradiol can be explained by two synergistic mechanisms: first, SHBG is able to bind estrogens in plasma thereby lowering their free fraction; second, pathways induced by binding of SHBG to the membranes of BRCA cells are known to cross-talk with estradiol-induced pathways and modify them in an antiproliferative way.…”
Section: Shbg and Cancermentioning
confidence: 99%